Determinants of Domestic Direct Investment in Indonesia: Islamic Economic Approach - Faizah, Iva; Fasa, Muhammad Iqbal; Suharto, Suharto; Rahmanto, Dhidhin Noer Ady; Athief, Fauzul Hanif Noor (Universitas Negeri Semarang, 2019)
The aim of this research is to analys the influence of Domestic Direct Investment (DDI) to Economic Growth in Indonesia (GDP) with Capital Expenditures as moderating variable. We use panel data with 9 years of observation (2010-2018) and 30 provinces in Indonesia, based on purposive sampling, secondary data and analyzed by MRA (Moderated Regression Analysis). The results indicates that, DDI actually gives negative effect on economic growth in Indonesia it was because of them is worth the investment in the country is still low when compared with foreign investment and investment out of the country, and greater fluctuations in value realization of these investments annually. Capital expenditure has proved to strengthen and change the direction of the relationship between the DDI to the GDP, due to the realization that capital spending is focused in the development of infrastructure.